The oncogenic roles of JC polyomavirus in cancer - Zheng, Hua-chuan; Xue, Hang; Zhang, Cong-yu (Frontiers in Oncology, 2022)
JC polyomavirus (JCPyV) belongs to the human polyomavirus family. Based on alternative splicing, the early region encodes the large and small T antigens, while the late region encodes the capsid structural proteins (VP1, VP2, and VP3) and the agnoprotein. The regulatory transcription factors for JCPyV include Sp1, TCF-4, DDX1, YB-1, LCP-1, Purα, GF-1, and NF-1. JCPyV enters tonsillar tissue through the intake of raw sewage, inhalation of air droplets, or parent-to-child transmission. It persists quiescently in lymphoid and renal tissues during latency. Both TGF-β1 and TNF-α stimulates JCPyV multiplication, while interferon-γ suppresses the process. The distinct distribution of caspid receptors (α-2, 6-linked sialic acid, non-sialylated glycosaminoglycans, and serotonin) determines the infection capabilities of JCPyV virions, and JCPyV entry is mediated by clathrin-mediated endocytosis. In permissive cells, JCPyV undergoes lytic proliferation and causes progressive multifocal leukoencephalopathy, while its DNA is inserted into genomic DNA and leads to carcinogenesis in non-permissive cells. T antigen targets p53, β-catenin, IRS, Rb, TGF-β1, PI3K/Akt and AMPK signal pathways in cancer cells. Intracranial injection of T antigen into animals results in neural tumors, and transgenic mice develop neural tumors, lens tumor, breast cancer, gastric, Vater’s, colorectal and pancreatic cancers, insulinoma, and hepatocellular carcinoma. Additionally, JCPyV DNA and its encoded products can be detected in the brain tissues of PML patients and brain, oral, esophageal, gastric, colorectal, breast, cervical, pancreatic, and hepatocellular cancer tissues. Therefore, JCPyV might represent an etiological risk factor for carcinogenesis and should be evaluated for early prevention, diagnosis, and treatment of cancers.